Systematic Literature Review: Penggunaan Wordwall dalam Meningkatkan Kemampuan Representasi Matematis dan Hasil Belajar Matematika - Abidah, Iffah; Iyan Rosita Dewi, Nur; Rika Mulyati Mustika, Sari (Department of Mathematics Education, Faculty of Tarbiyah and Teacher Training, UIN Sunan Ampel Surabaya, 2025)
This study aims to review the impact of Wordwall on students’ mathematical representation skills and learning outcomes through a Systematic Literature Review (SLR). Seventeen articles published between 2018 and 2024 were selected as research objects, focusing on the implementation of Wordwall in mathematics learning at the elementary and junior high school levels. Data were collected using the Publish or Perish application to search databases with the keywords “Wordwall,” “learning outcomes,” and “mathematical representation,” followed by a relevance-based screening process according to inclusion criteria. The data were analyzed thematically by categorizing studies based on their focus, comparing findings, and synthesizing key results. The review reveals that Wordwall consistently has a favorable and noteworthy impact on students' visual, symbolic, and verbal mathematical representations as well as their overall learning outcomes. Furthermore, Wordwall serves not just as an engaging quiz tool but also as a core pedagogical component that guides learning, increases motivation, and enhances active participation, indicating its potential as an effective and flexible digital learning medium to improve conceptual understanding in mathematics.